OPTIMALISASI KONTRIBUSI PERGURUAN TINGGI DALAM MEMBERANTAS KORUPSI DI ACEH - M. Shabri Abd. Majid (Jurnal Pencerahan, 2013)
Aceh is known as the most religious province in Indonesia, which has been granted by the central government, Jakarta to implement Islamic law in regulating the state affairs. Ironically, the province has been ranked as the third corrupted province in Indonesia. This study analyse descriptively the role of the higher education institutions in combating the corruption in Aceh. The efforts to empower the universities in combating the corruption were proposed in the study. The universities are supposed not only to transfer knowledge but it also to transfer the values. The universities should educate student to become a good citizen, intellectually and spiritually. The values, norms, and Islamic ethics should be inculcated into the students during the studying and learning process at the universities. The content of the curricula needs to be developed, inculcating these Islamic values, i.e., amanah (trustworthy), honesty, responsibility, ikhlas (sincerity), ihsan (benevolent), ‘adil (just), and teaching for the sake of Allah. It is strongly believed that by inculcating Islamic principles and values into the students’ mind, the university graduates will be able to free themselves from any corrupted activities and even they emerge as the heroes who readily stand in forefront to combatcorruption in Aceh.